The Effect of Hay The Java Wood Leaves (Lannea coromandelica) on Weight Addition, Dry Material Consumption and Efficiency of Local Goat Feed - Syafira, Syafira; Syahrir, Syahrir (FAPETKAN UNTAD, 2020)
This study aims to determine the response to body weight gain, feed consumption and feed efficiency of goat nuts fed with Javanese wood leaf hay (Lannea coromandelica). This research was conducted on 24 November 2019 to 02 February 2020 at the CV. Prima BREED Tondo Village, Mantikulore Subdistrict, Palu City, Central Sulawesi Province. The livestock used in this study were 12 female local goats aged 10 months with a body weight range between 11.29 - 16.29 kg, which were placed in individual cages with wooden floors. 12 plots are made. This study conducted a comparison test of 2 treatments with t-test statistical analysis. The treatments tested were P1 = Giving concentrate without Java wood leaf hay, P2 = Giving concentrate + 0.5% Java leaf hay. The variables observed were body weight gain, dry matter consumption of rations, and efficiency of ration use. The results showed that giving of Java wood leaf hay had no significant effect on body weight gain and ration efficiency, but had a significant effect on the consumption of dry matter.